Near fatal fall complicated by penetrating neck injury with uneventful outcome: a case report - Nabeel, A; Irfan, M (Bangladesh Journal of Medical Science, 2011)
Fall from height is commonly associated with long bones fractures or neurological compromised outcome. On the other hand, penetrating neck injury is linked to life threatening complications especially when the injury involves major blood vessels, spinal cord, cervical spines and aerodigestive tracts. However, in some rare circumstances, a patient may suffer both the eventful fall from height complicated with penetrating neck injury. We report a patient who presented with a wooden stick passing through the lateral side of his neck after an episode of fall. He survived without any residual complications. Keywords: Fall; penetrating neck injury. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7808 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.125-128